2007
DOI: 10.1021/je060278s
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Activity Coefficients for Cesium Chloride in Methanol−Water and Ethanol−Water Mixed Solvents by Electromotive Force Measurements at 298.15 K

Abstract: Activity coefficients for CsCl in different methanol-water and ethanol-water mixed solvents were determined at 298.15 K by electromotive force (EMF) measurements of the cell: Cs-ISE|CsCl (m), alcohol (Y), H 2 O (100 -Y)|Ag|AgCl. The cesium ion-selective electrode (Cs-ISE) and the Ag|AgCl electrode used in this work were made in this laboratory and had good Nernstian response. The experimental data were calculated using the Pitzer model. Standard cell potentials and Pitzer parameters were obtained. From these, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…10,11 The Cs-ISE was prepared by ourselves. 14 The Br-ISE (model 302) was obtained from Jiangsu Electroanalytic Instrument Factory.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 The Cs-ISE was prepared by ourselves. 14 The Br-ISE (model 302) was obtained from Jiangsu Electroanalytic Instrument Factory.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, probing into the nature of interactions between amides and electrolytes is important for the design of suitable processes for its application. For example, Hernández-Luis et al carried out a series of systematic studies of electrolyte NaF/NaCl/NaBr in formamide–water mixtures. In recent years, our research group investigated the thermodynamic properties of heavy alkaline metal chlorides and fluorides in organic–water with ε-increasing and ε-decreasing cosolvents such as alcohol–water, amino acid–water, and amide–water et al The solution properties of aqueous mixtures of formamide–water and urea–water have received considerable attention in the literature. , The results showed that the dielectric constants (ε-increasing and ε-decreasing cosolvents) of the mixed solvents had a great effect on the thermodynamic properties of the systems.…”
Section: Introductionmentioning
confidence: 99%
“…It might be because of their application for developing electrolyte solution theories, research in biochemistry, environmental chemistry, oceanography, geochemistry, industrial chemistry, chemical and biological industries and electroanalysis [1][2][3][4][5][6][7]. Activity coefficients and other thermodynamic properties such as osmotic coefficients and excess Gibbs free energy allow us to analyze the deviation of a real solution from ideality [1,4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Both are useful experimental techniques. The electromotive force (EMF) is one of the best methods because of its simplicity, high speed, accuracy, stability in measured potentials, and possibility of measurement in wider concentration range particularly in diluted ranges [1][2][3][4][5]. Potentiometric sensors detect the relationship between the activity of the species and the observed potential response with the two-electrode system comprising an indicator electrode and a reference electrode [8].…”
Section: Introductionmentioning
confidence: 99%